1892. Preparing for an Antibiotic Stewardship Intervention Through Nursing Surveys of Knowledge and Safety. (26th November 2018) - Trautner, Barbara W; Drekonja, Dimitri M; Patel, Payal; Graber, Christopher J; Gauthier, Timothy; Rosen, Tracey; Dillon, Laura; Lichtenberger, Paola; Naik, Aanand; Grigoryan, Larissa
Abstract: Background: We designed an intervention to reduce unnecessary antibiotic treatment of asymptomatic bacteriuria (ASB), by decreasing unnecessary urine cultures. Nurses and clinical nurse assistants (CNAs) play important roles in requesting urine cultures. As preparation for the intervention, we assessed knowledge of the appropriate indications for urine cultures among these personnel while measuring their safety climate. Methods: Surveys were administered to licensed nursing personnel (RN, LPN, and NP) as well as to CNAs on all acute medical and long-term care units of four VA facilities across the nation. Surveys combined two validated subcomponents: knowledge of ASB and safety attitudes. Knowledge questions, which differed in emphasis between the licensed personnel and the CNAs, focused on indications for urine cultures. Safety questions were the teamwork climate and safety climate domains from the Safety Attitudes Questionnaire. Surveys were administered on paper during January–April 2018. Results: We received 110 responses from licensed nursing personnel and 40 from CNAs. The response rate on distributed surveys was 110/140 (79%) for licensed personnel and 40/50 (80%) for CNAs. 94% of nurses and 73% of CNAs correctly recognized fever as an indication for urine culture. Many also endorsed incorrect triggers for urine cultures: cloudy urine (80% of nurses, 55% of CNAs), foul-smelling urine (87% of nurses, 85% of CNAs), and a change in color (44% of nurses, 73% of CNAs). 50% of nurses endorsed screening urine cultures on admission of catheterized patients. Scores on the teamwork climate (highest possible score 100) were 70 for nurses and 79 for CNAs; scores on the safety climate were 70 for nurses and 78 for CNAs. Conclusion: This multicenter survey identified actionable gaps in knowledge about when to send urine cultures among nursing personnel in acute medical and long-term care units. However, scores on teamwork and safety climate were high, suggesting that these personnel have an effective voice in patient safety. Together our survey results indicate that empowering the personnel at the bedside to discourage unnecessary urine culturing should be a key component of our stewardship intervention. Disclosures: B. W. Trautner, Paratek: Consultant, Consulting fee. Zambon: Consultant, Consulting fee and Research grant.